2012
DOI: 10.1134/s0021364012060112
|View full text |Cite
|
Sign up to set email alerts
|

Berry effect in unmagnetized inhomogeneous cold plasmas

Abstract: The propagation of electromagnetic waves in an unmagnetized weakly inhomogeneous cold plasma is examined. We show that the inhomogeneity induces a gauge connection term in wave equation, which gives rise to Berry effects in the dynamics of polarized rays in the post geometric optics approximation. The polarization plane of a plane polarized ray rotates as a result of the geometric Berry phase, which is the Rytov rotation. Also, the Berry curvature causes the optical Hall effect, according to which, rays of lef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Experimentally, the r.m.s fluctuations given by (21) corresponds to the standard deviation of a large data sample {x i ⊥ } collected over time from a cosmically distant source of circularly polarized radiation, x i ⊥ being the position of the point (with respect to the origin, i x i ⊥ = 0) where the fluctuating ray (of a given wavelength) hits the transverse 'photographic plate' at time i (FIG. 2).…”
Section: Conformally Invariant Primordial Inhomogeneitymentioning
confidence: 99%
See 2 more Smart Citations
“…Experimentally, the r.m.s fluctuations given by (21) corresponds to the standard deviation of a large data sample {x i ⊥ } collected over time from a cosmically distant source of circularly polarized radiation, x i ⊥ being the position of the point (with respect to the origin, i x i ⊥ = 0) where the fluctuating ray (of a given wavelength) hits the transverse 'photographic plate' at time i (FIG. 2).…”
Section: Conformally Invariant Primordial Inhomogeneitymentioning
confidence: 99%
“…The present work is motivated by the fact that inhomogeneity in propagation medium generally leads to spin transport effects [15][16][17][18][19][20][21]. We, thus, consider the effect of the spatial fluctuations of the axion field that have survived the inflation, on the spin (polarization) transport of light.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the dependence on polarization of optical and transverse acoustical wave propagation in inhomogeneous media, there occurs similar polarization rotation (the Rytov rotation), which is established to be a manifestation of the Berry phase of the quanta (photons/phonons) of the quantized wave fields [12][13][14]. In this work, we show that the cosmological birefringence likewise arises from an adiabatic noncyclic geometric phase that appears in the quntum state of the photons because of their interaction with the slowly varying pseudo-scalar field.…”
Section: Introductionmentioning
confidence: 99%
“…This change is due to Dirac phase and is robust against fluctuations. Dirac phase belongs in the category of non-integrable phase factors that appear in many different areas of Physics [31][32][33]. Dirac showed that when a particle transports in an external electromagnetic field, its wave function acquires a phase term in addition to usual dynamic phase factor [34,35].…”
Section: Introductionmentioning
confidence: 99%